TalkED: A Video Conferencing Tool for Online Learning in Response to Education Technology Amidst the COVID-19 Pandemic - Abaya, Sheila A; Besana, Allyssa Thea J; Ceballos, Christian Jude G; Cruz, Christelle Alaine P; Jubilo, Raya J; Piamonte, Carla Angela V (International Journal of Publication and Social Studies, 2022)
Video conferencing enables people to conduct live communication regardless of their location. Due to the COVID-19 pandemic, video conferencing tools became the new way of communicating in workplaces and became part of online distance learning in the academic community. Since the researchers were entities in the academe who were mainly affected by the pandemic, it opened the opportunity for the development of a video conference tool that their institution could use without recurring much acquisition or operational cost. The tool provides real-time interaction between users in an unlimited time of discussion. The tool provides chat-box, screen-sharing and whiteboard features. Unlike the usual conferencing tools, the proposed tool is innovated with new features of sharing files, poll creation when asking questions and a word cloud. The tool was evaluated by several students and professors of the University of the East, Caloocan through the criteria of: interactivity, usability and interface consistency.